2004
DOI: 10.1586/14737140.4.4.543
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 and its inhibition as a molecular target in the prevention and treatment of lung cancer

Abstract: Lung cancer is the leading cause of cancer death in the USA. Conventional therapy using chemotherapy, radiation therapy, and a combination of the two, has yielded modest improvement in patient outcome. Dysfunction and dysregulation of many molecular processes and signaling pathways are involved in the development and growth of malignant lung tumors, and in conferring resistance to standard cancer treatments. Cyclooxygenase (COX)-2, an enzyme involved in prostaglandin production in pathologic states, is often o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 88 publications
(112 reference statements)
0
15
0
Order By: Relevance
“…A role for CD40 in inflammation is highlighted by the observation that CD40 engagement induces the synthesis of the proinflammatory cyclooxygenase-2 (COX-2)/prostaglandin E2 system in lung fibroblasts and disruption of the constitutive CD40-CD40L pathway reduces lung inflammation and fibrosis (Adawi et al, 1998;Zhang et al, 1998). Similarly, COX-2 inhibitors confer therapeutic benefits for the treatment of lung cancer (reviewed by Liao and Milas, 2004). A recent report has demonstrated that NF-kB is a critical link between inflammation and cancer, promoting the conversion of chronic inflammatory liver disease to hepatocellular carcinoma in a mouse model (Pikarsky et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A role for CD40 in inflammation is highlighted by the observation that CD40 engagement induces the synthesis of the proinflammatory cyclooxygenase-2 (COX-2)/prostaglandin E2 system in lung fibroblasts and disruption of the constitutive CD40-CD40L pathway reduces lung inflammation and fibrosis (Adawi et al, 1998;Zhang et al, 1998). Similarly, COX-2 inhibitors confer therapeutic benefits for the treatment of lung cancer (reviewed by Liao and Milas, 2004). A recent report has demonstrated that NF-kB is a critical link between inflammation and cancer, promoting the conversion of chronic inflammatory liver disease to hepatocellular carcinoma in a mouse model (Pikarsky et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that an adjuvant treatment with COX inhibitors may increase the therapeutic efficiency of distinct chemotherapeutic agents and radiation. 87 5-or 12-LOX inhibitors were reported to induce apoptosis in human breast, gastric, hepatocellular, pancreatic and prostate cancer cells. 35,36 In human breast cancer cells, both 5-LOX and 12-LOX inhibitors induce apoptosis through cytochrome c release and caspase 9 activation whereas 5-HETE and 12-HETE stimulate proliferation of this cells.…”
Section: Tumor Cell Survivalmentioning
confidence: 99%
“…Selective COX-2 inhibitors are tested in clinical trials for prevention and tumor therapy (47)(48)(49) and preclinical data suggests that COX-2 inhibitors might act additively or synergistically with the specific chemotherapeutic agents used in the treatment of these tumors.…”
Section: Pge 2 Leads To Inhibition Of Cd4mentioning
confidence: 99%